PEMURNIAN SELULASE DARI ISOLAT KB KOMPOS TERMOFILIK DESA BAYAT KLATEN MENGGUNAKAN FRAKSINASI AMONIUM SULFAT - Sinatari, Hanum Mustika (Chem Info Journal, 2013)
Purification of cellulase enzymes derived from KB thermophilic composting isolates of Bayat Klaten using fractionation ammonium sulphate needs to be done so that cellulase can cuts cellulose chains more effectively. This study aims to gain cellulases from KB thermophilic composting isolates of Bayat Klaten is more pure than the crude cellulase extract. Purification of cellulases from KB isolates using fractionation ammonium sulphate with saturation 0-20% (F1), 20-40% (F2), 40-60% (F3), 60-80% (F4), and 80-100% (F5), followed by cellulase dialysis using cellophane membranes. Cellulases fractions activity was measured using Dinitrosalicylic acid (DNS) method and Lowry method. This study obtained cellulase with specific activity in the crude extract cellulase of 0.212 units/mg protein and the highest enzyme specific activity in fraction 2 (20-40% ammonium sulphate) of 0.749 U/mg protein. The specific activity of cellulase in fraction 2 increased 3,5 times from the specific activity of the crude cellulase extract. Â